Effects of mechanical stimulation on the reprogramming of somatic cells into human-induced pluripotent stem cells - Young Mi Kim; Yun Gyeong Kang; So Hee Park; Myung-Kwan Han; Jae Ho Kim; Ji Won Shin; Jung-Woog Shin (Stem Cell Research & Therapy, 2017)
Abstract Background Mechanical stimuli play important roles in the proliferation and differentiation of adult stem cells. However, few studies on their effects on induced pluripotent stem cells (iPSCs) have been published. Methods Human dermal fibroblasts were seeded onto flexible membrane-bottom plates, and infected with retrovirus expressing the four reprogramming factors OCT4, SOX2, KLF, and c-MYC (OSKM). The cells were subjected to equiaxial stretching (3% or 8% for 2, 4, or 7 days) and seeded on feeder cells (STO). The reprogramming into iPSCs was evaluated by the expression of pluripotent markers, in vitro differentiation into three germ layers, and teratoma formation. Results Equiaxial stretching enhanced reprogramming efficiency without affecting the viral transduction rate. iPSCs induced by transduction of four reprogramming factors and application of equiaxial stretching had characteristics typical of iPSCs in terms of pluripotency and differentiation potentials. Conclusions This is the first study to show that mechanical stimuli can increase reprogramming efficiency. However, it did not enhance the infection rate, indicating that mechanical stimuli, defined as stretching in this study, have positive effects on reprogramming rather than on infection. Additional studies should evaluate the mechanism underlying the modulation of reprogramming of somatic cells into iPSCs.